Stereotypes from the Inside: Chinese International Students’ Experiences with Peers’ Outgroup Favoritism - Ji, Yadong (Journal of International Students, 2021)
Communication scholars often examine immigrants’ ingroup favoritism to study their intergroup/intercultural communication. Less is known about how some immigrants exhibit outgroup favoritism for the host culture and how outgroup favoritism relates to their ingroup communication. Drawn upon literature on outgroup favoritism, this study understands international/intercultural communication in a global system where some immigrants favor the hosting outgroup. The researcher investigates how Chinese international students experience their peers’ performance of outgroup favoritism in the United States. Through in-depth interviews (n = 15), this study identifies how outgroup favoritism enacts negative ingroup stereotyping and ingroup distancing. Students with outgroup favoritism strategically negotiate for less ingroup membership and more outgroup affiliation, creating mutual exclusion among ingroup members. Discussion focuses on Chinese international students’ communication dilemma with outgroup-favoring ingroup members.